Design and evaluation of osmotic pump tablets of naproxen sodium - Ramakrishna N.; Mishra B. (My University, 2025)
Osmotic pump tablets (OPTs) deliver a constant, predetermined amount of drug in solution form over a fixed span of time, independent of external environmental conditions. OPTs of naxopren sodium (NPS) were made and evaluated with the principal aim of limiting the drug's frequently experienced gastrointestinal side effects, by preventing the undissolved drug from coming in to contact with the gastric mucosa. OPTs with and without the osmotic driving agent, sodium chloride (SCL), with different membrane thicknesses, and with and without an orifice were designed. In vitro release profiles of the OPTs, when compared to a conventional marketed tablet (Xenobid® 275), were highly controlled and exhibited an almost perfect zero-order release pattern. The magnitudes of lag times and average release rates were found to depend on the amount of SCL present in the formulation which decreased the drug's solubility within the system. The release rates were found to be independent of stirring rate and decreased with increasing membrane thickness. Release profiles of the OPTs with and without an orifice were found to be comparable.